When third space is more than the library: The complexities of theorising and learning to use family and community resources to teach elementary literacy and mathematics - Norton-Meier, L; Drake, C (2008)
In this paper, we examine theory and practice related to creating spaces for pre-service teachers to learn about incorporating family and community resources into elementary mathematics and literacy. Our framework for understanding pre-service teacher learning related to families and communities as resources for both mathematics and literacy instruction locates this learning as happening concurrently in an elementary school, in the community in which the elementary school is located, and in university classrooms. Furthermore, we operationalize teacher learning as changes in: personal narratives of self as a learner and teacher; professional identities and practices as elementary teachers; understandings of the mathematics and literacy practices and resources of children, families, and communities. We are especially interested in understanding the 'third spaces' and overlaps that are highlighted by this model of teacher learning. In particular, in this paper, we are focusing on the overlaps inherent in the last element of pre-service teacher learning - related to the literacy and mathematics practices and resources of children, families, and communities - and the tensions, challenges, and benefits of exploring and supporting pre-service teachers in learning about these overlaps in three intersecting spaces - elementary school, community, and university.